From the Editor - Judith A. Holton (Grounded Theory Review: An International Journal, 2010)
Two particular challenges for which novice grounded theorists often seek advice and assistance occur at the outset and at the end of the research process – seeking institutional approval to undertake data collection and, as work progresses, the process of writing conceptually. In this issue, both novice and experienced grounded theorists offer perspectives and suggestions on both, grounded in their own experiences.